2023
DOI: 10.3390/ijms241210185
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Extract from Wastes of Edible Flowers and Snail Mucus Ameliorate Ultraviolet B-Induced Damage in Keratinocytes

Luca Vanella,
Valeria Consoli,
Ilaria Burò
et al.

Abstract: Several studies have highlighted the ability of snail mucus in maintaining healthy skin conditions due to its emollient, regenerative, and protective properties. In particular, mucus derived from Helix aspersa muller has already been reported to have beneficial properties such as antimicrobial activity and wound repair capacity. In order to enhance the beneficial effects of snail mucus, a formulation enriched with antioxidant compounds derived from edible flower waste (Acmella oleracea L., Centaurea cyanus L.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…It has been reported that snail mucus is able to counteract the damage generated by free radicals thanks to the presence of hyaluronic acid and antioxidants (Conte et al ). As previously reported, 24 low levels of polyphenols justified the poor antioxidant activity of SEM provided by “La lumaca Madonita”. To enhance antioxidant activity of snail mucus, it was extracted in a hydroalcoholic solution and subsequently freeze-dried.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…It has been reported that snail mucus is able to counteract the damage generated by free radicals thanks to the presence of hyaluronic acid and antioxidants (Conte et al ). As previously reported, 24 low levels of polyphenols justified the poor antioxidant activity of SEM provided by “La lumaca Madonita”. To enhance antioxidant activity of snail mucus, it was extracted in a hydroalcoholic solution and subsequently freeze-dried.…”
Section: Resultssupporting
confidence: 73%
“…Snail mucus extraction was performed according to a cruelty-free system using the patented extractor machine EXTRACTA as reported in our previous study. 24 Snail Mucus Extract was prepared from Snail Mucus mixed with 60% hydroalcoholic solution (food grade) and then filtered. The filtrate was concentrated at low temperature to remove the solvent and then spray-dried to obtain the standardized extract.…”
Section: Methodsmentioning
confidence: 99%
“…Some bioactive compounds in gastropod mucus also exhibit antioxidant activities, including certain peptides and polyphenols. 5,72 In canine skin cell models, secretion filtrate from snail mucus reduced the production of inflammatory mediators implicated in atopic dermatitis, including cytokines like IL-6, IL-8, and IL-17A. 73 These antiinflammatory effects suggest the potential for snail mucus components as natural therapeutic agents for inflammatory skin conditions in veterinary species.…”
Section: Acs Biomaterialsmentioning
confidence: 99%
“…In vitro studies illustrated that antioxidant-rich edible flower waste extracts amplify the cytoprotective effects of snail mucus against UVB-induced damage in keratinocytes, as evidenced by enhanced antioxidant activity, reduced glutathione content, ROS, and lipid peroxidation levels, thereby suggesting potential cosmeceutical applications for flower waste. 72 Finally, most mollusc mucus demonstrates broad-spectrum antimicrobial and anti-inflammatory properties, 50,76,77 conferring preservative effects against contaminants in cosmetics. However, antimicrobial efficacy varies widely between species and individuals.…”
Section: Acs Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation